Early efficacy of teprotumumab for the treatment of dysthyroid optic neuropathy: A multicenter study - Sears, Connie M. (Am J Ophthalmol Case Rep, 2021)
PURPOSE: To study post-interventional findings in patients with dysthyroid optic neuropathy (DON) treated with teprotumumab. OBSERVATIONS: In this multicenter observational Case series, patients with DON were treated with teprotumumab, an insulin-like growth factor I receptor inhibitor (10 mg/kg for the first infusion then 20 mg/kg for subsequent infusions, every three weeks for a total 8 infusions). This study included patients with acute and chronic thyroid eye disease (TED) with DON who had failed conventional therapies and were not candidates for surgical decompression. Data collected included best corrected visual acuity (BCVA), color vision, RAPD when present, and orbital CT or MRI. Proptosis, clinical activity score (CAS), Gorman diplopia score (GDS), and Humphrey visual fields (HVF) were also evaluated. Ten patients (6 women, 4 men) with an average age 64 years old were included in this study. Mean follow up after completion of infusions was 15 weeks. Baseline visual acuity (VA) impairment ranged from hand motion (HM) to 20/25 in affected eyes. All patients had pre-treatment orbital CT or MRI that confirmed orbital apex compression. Seventy percent of patients had objective improvement in DON after 2 infusions of teprotumumab measured as significant improvement in visual acuity, resolution of RAPD, or both. After completion of treatment, affected eyes had a mean BCVA improvement of 0.87 logMAR (p=0.0207), proptosis reduction of 4.7 mm (p<0.00001), CAS improvement of 5.25 points (p<0.00001), and GDS improvement of 0.75 points (p=0.160). All 6 patients who presented with an RAPD had resolution or improvement of RAPD. All 7 patients who presented with color vision deficits had normalization or improvement of color vision. CONCLUSIONS AND IMPORTANCE: Teprotumumab infusions resulted in medical decompression and objective resolution or improvement of dysthyroid optic neuropathy. Most patients had rapid improvement of visual acuity and reversal of RAPD. Post-infusion imaging demonstrated reduction in extraocular muscle size that correlated with improvement in visual dysfunction. However, patients who presented with longstanding severe visual loss had limited improvement. There was no recurrence of DON after completion of teprotumumab in our cohort.